Evaluating the role of partnerships in increasing the use of big Earth data to support the Sustainable Development Goals: an Australian perspective. Issue 4 (26th November 2021) - Mohamed-Ghouse, Zaffar Sadiq; Desha, Cheryl; Rajabifard, Abbas; Blicavs, Michelle; Martin, Graeme
ABSTRACT: Leaders are increasingly calling for improved decision support to manage human and environmental challenges in the 21 st Century. The 17 United Nations Sustainable Development Goals (SDGs) provide a framing of these challenges, wherein 169 targets require significant data to be monitored and pursued effectively. However, many targets are still not connected with big Earth data capabilities. In this conceptual paper, the authors sought to answer the question "How are partnerships influencing progress in using big Earth data to address the SDGs?" Using the Pivotal Principles for Digital Earth, we reflect on the geospatial sector's partnering efforts and opportunities for enhancing the use of big Earth data. We use Australia as a case study to explore partnering for action towards one or more SDGs. We conclude that partnerships are emerging for big Earth data use in addressing the SDGs, but much can still be done to harness the power of partnerships for transformative SDG outcomes. We propose four key enabling priorities: 1) multiple-stakeholder collaboration, 2) regular enactment of the problem-solving cycle, 3) transparent and reliable georeferenced data, and 4) development and preservation of trust. Five "next steps" are outlined for Australia, which can also benefit practitioners and leaders globally in problem-solving for the SDGs.